'Large Is Beautiful!' Associative Retraining Changes Implicit Beliefs About Thinness and Beauty and Decreases Women's Appearance Anxiety. Issue 1 (17th February 2021) - Selimbegovic, Leila; Collange, Julie; Bocage-Barthélémy, Yvana; Chatard, Armand
The present research aimed to investigate whether retraining thin-beautiful associations could modify implicit beliefs relating thinness to beauty, increase me-beauty associations, and decrease explicit body anxiety in young women. In Experiment 1 (N = 180 women), participants were repeatedly exposed to beauty-related words paired with thin-related or large-related words on 50% (control) versus 75% (retraining) of trials. Implicit belief was assessed with a Relational Responding Task. In Experiment 2 (N = 195 women), me-beauty associations were assessed with a single-category Implicit Association Task, and body anxiety with a self-report measure. The implicit association measure remained unaffected by the retraining task. However, after retraining, women displayed weaker thin-is-beautiful implicit belief, Cohen's d = 0.44, CI95 [0.14, 0.74], and less body anxiety, Cohen's d = 0.34, CI95 [0.06, 0.63] than in the control condition. These results suggest that retraining thin-beautiful associations could reduce thin-is-beautiful implicit beliefs and decrease explicit body anxiety among women.